THE EFFECT OF INFILL PATTERN AND DENSITY PARAMETERS ON TENSILE STRENGTH OF POLYMER MATERIALS IN 3D PRINTING - Cahyati, Sally; Putra, Reky Amanda (Jurnal Rekayasa Mesin, 2023)
One of the references for selecting materials in designing a machine component is its mechanical property which is tensile strength. However, the current tensile strength from the materials used in 3D printing products has not been standardized due to many parameters in the design and process that affect them. The selection of correct design and process parameters may result in the proper mechanical properties and minimize the time and amount of materials used during the printing process. The parameters expected to affect the mechanical properties are density and infill pattern. This study was conducted to observe how far the effect of them on the mechanical properties of 3D printing product's tensile strength. The specimen standard of tensile strength used was ASTM D638, while the tested infill pattern was Grid, Triangles, and Tri-Hexagon patterns, with the percentage of total infill density of 20%, 40%, and 60%. PLA (Polylactic Acid) was chosen as the material used in this study. The 3D print machine operated was 3D Print MakerGear M2 with the tensile testing machine of HTE Hounsfield. The results of this study concluded that the percentage of infill density 20%, 40%, and 60% with different infill patterns had different tensile strengths. The specimen with a Tri-Hexagon infill pattern and 60% density had the biggest tensile strength value, followed by the Triangles infill pattern and the smallest one was the Grid pattern with 20% density.